2021
DOI: 10.21203/rs.3.rs-94534/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atypical Deletion of Williams-beuren Syndrome Reveals the Mechanism of Neurodevelopmental Disorders

Abstract: Background The Williams-Beuren syndrome (WBS) is a multiple phylogenetic disorder, caused by the hemizygous deletion of 1.55 to 1.84 Mb on chromosome 7q11.23, which encodes a fragment of 26 to 28 genes. Among these genes, the deletion of the elastin (ELN) gene haplotype is the main cause of cardiovascular abnormalities. Other genes, such as CLIP2, GTF2IRD1, and GTF2I, may be associated with specific cognitive and craniofacial features. However, genes associated with specific neurocognitive phenotypes are still… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recently, it has been revealed that native vesicle docking can be mediated by a single trans binary Sx1A-Sb2 complex in the absence of SNAP25 [39,40]. And STX1A may be involved in Williams-Beuren syndrome and Parkinson's disease [41,42]. To date, the link between STX1A and dopaminergic neurons is not fully disclosed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been revealed that native vesicle docking can be mediated by a single trans binary Sx1A-Sb2 complex in the absence of SNAP25 [39,40]. And STX1A may be involved in Williams-Beuren syndrome and Parkinson's disease [41,42]. To date, the link between STX1A and dopaminergic neurons is not fully disclosed.…”
Section: Discussionmentioning
confidence: 99%